A study on the relationship between perceived training and organizational commitment among fresh graduates in China - Jiawei, Li (2017)
The objective of the study was to study the relationship between perceived training and organizational commitment among fresh graduates in China. The research question of the study is: To what extent are training perceptions related to organizational commitment among Chinese fresh graduates? Specifically, five dimensions of perceived training i.e. (Motivation to Learn, Access of Training, Perceived Benefits of Training, Perceived Co-worker Support for Training, Perceived Supervisor Support for Training) were adopted to measure how fresh graduates perceived firm-provided training, and two forms of organizational commitment (affective and continuance commitment) were selected to analyze the impact of perceived training on graduates' organizational commitment. Even though the study may only make limited contributions to the field of knowledge, the research offered some understandings of the relationship between perceived training and organizational commitment among fresh graduates in the context of China, which has been found of limited evidence in the literature. In addition, the study offered managerial implications for employers who want to hire Chinese fresh graduates and also improve their organizational commitment in order to improve the performance of graduates and develop the sustainable competitive advantages of the organization. The hypotheses were tested through quantitative method. Online survey was conducted in China with 165 respondents participated in the study. Results of the study showed significant positive relationship between affective commitment and five dimensions of perceived training, while partially significant positive relationship between continuance commitment and perceived training, where only perceived benefits of training and co-worker support for training were positively significantly related to continuance commitment.